Evaluating the Social and Economic Impacts of Rural Road Improvements in the State of Tocantins, Brazil - Iimi, Atsushi; Lancelot, Eric; Manelici, Isabela; Ogita, Satoshi (World Bank, Washington, DC, 2015)
The aim of this paper is to provide feedback on the question of socioeconomic benefits from rural road development and the impact of transport infrastructure on the poor, particularly the poorest and the bottom 40 percent of the population. This study relies on impact evaluation methodologies, which are traditionally used in social sectors but less so in the transport sector. These methodologies were launched in 2003 under the Tocantins sustainable regional development project. This paper highlights the context that led to the project’s design, which included an impact evaluation of the works envisaged under the project. It also highlights some of the main challenges faced by this impact evaluation and how these challenges were addressed for the present study. It then provides details about the data collected during the surveys and the key relevant characteristics of the population targeted by the surveys. It discusses the possible estimation methods envisioned to undertake the study and provides the main results of the assessment based on these methods. The analysis shows that improved rural roads changed people’s transport modal choice. People came to use more public buses and individual motorized vehicles after the rural road improvements. The paper also finds that the project increased school attendance, particularly for girls. Although the evidence is relatively weak in statistical terms, it indicates that the project contributed to increasing agricultural jobs and household income in certain regions.